المادة التعليمية للغة العربية على أسس قيم الألعاب التقليدية بإندونيسيا - Nur laila rahmawati (LISANIA: Journal of Arabic Education and Literature, 2018)
This research aims to develop Al-'Arabiyyah Li al-Athfâl (ALA) Learning Materials based on Indonesian Traditional Games for students of Arabic Education Department STAI At-Tanwir Bojonegoro by producing book and to know the validity and feasibility of Al-'Arabiyyah Li -Athfâl (ALA) based on Indonesian Traditional Games for students of students of Arabic Education Department STAI At-Tanwir Bojonegoro Arabic Study Program. The type of research used is research and development of ADDIE (Analyze, Design, Develop, Implement, Evaluate) model. The types of data include quantitative and qualitative, while data collection instruments used are questionnaires and interviews and to be analyzed by using descriptive and qualitative statistical analysis. The results show that book produced is valid and feasible to be used in Arabic learning process, seen from expert test analysis and user response test.